CANDIDATE GENES IDENTIFICATION OF OIL PALM (Elaeis guineensis Jacq.) INTEREST CHARACTERS USING PUBLISHED DATABASE - Sarimana, Upit; Putro Priadi, Dwi; Hasmeda, Mery; Erika, Pratiwi; Herrero, Javier; Santika, Baitha; Wendra, Fahmi; Sembiring, Zulhermana; Asmono, Dwi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2021)
Palm oil has supplied more than 30% of vegetable oil consumption worldwide. Rising demand has pushed oil palm plantations to increase the yield. It is well known that genetic has played a significant role in phenotypic performance. Moreover, in recent years, genomic data has emerged tremendously. Unfortunately on the gene related to oil palm yield. Therefore, a preliminary study to classify and select oil palm candidate genes associated with characteristic by scanning existing genes in oil palm or other in-silico species were conducted. Based on Blast2Go results, 22 genes related to oil biosynthesis, two specifically related to fruit number and fruit weight were analysed. Furthermore, 19 candidate genes were able to amplify.